Impacto dos genes cag-pai (caga, cage e virb11) e vaca do helicobacter pylori na patogênese de adenocarcinomas gástricos - Lima, Valeska Portela (2008)
The gastric cancer is the fourth more frequent cancer, and the second cause of death for cancer in the world, recording approximately 934 thousand of new cases and 700 thousand of deaths a year. In Brazil, the gastric cancer is the sixth more frequent malignant tumor. In the Northeast area, it is the second more frequent cancer among the men and fourth among the women. In the state of Ceara, it is the third more frequent neoplasia. Among the infectious agents, the bacterium Helicobacter pylori (H. pylori), which is considered carcinogenic agent of the group I, has been pointed in the last decades because of the connection with activated chronic gastritis, with the development of peptic ulcers and duodenais, and the increase of the risk of gastric cancer. Besides the presence, genetic variation of the strains of H. pylori seems to influence in the seriousness of the disease caused by infection. The pathogenic character is given by the presence, in some cepas, of the called cag pathogenicity island, cag-PAI; one gene fragment of 35-40 Kb strain specific, which possess a series of genes associates to a virulent type IV secretion apparatus. Moreover, another gene, called vacA, it is presented as an important virulence factor. Despite these associations does not have still a direct relation enters the presence of these genes with the tumorigenic process. One of the possible explanations is the presence of other genes that contribute for fenotype more serious or malignant, mainly associates cag-PAI. In this context, the present study objectified to investigate the frequency of H. pylori genotyped how much the alelics variants of vacA the presence of the genes cagA, cagE and virB11 and its association with the clinic- pathological dates of gastric adenocarcinoma of one population of the Ceara State. For in such a way, 101 cases of gastric adenocarcinoma (68 men and 33 women), gotten of two hospitals of Fortaleza, had been analyzed by PCR how much to the presence of H. pylori and the studied genes. The distribution of the gastric cancer by sex, anatomical sites and the histopatologic analysis, in general way, had reproduced the trends of world-wide literature. The bacterium was present in 93% of the analyzed cases. The genes of H. pylori had presented the following frequencies: vacAs1m1 (75,5%), vacAs1m2 (13,8%), vacAs2m1 (4,6%), vacA s2m2 (6,5%), cagA (64,9%), cagE (53,2%) and virB11 (60,6%). These data are the first ones in world-wide literature citing the frequency of virB11 and as for the gene cagE in gastric cancer and indicate a circulating variation of strains how much the presence of these genes when compared these data with the ones of other gastric diseases. The most frequent combination was vacAs1m1cagA(+)cagE(+)virB11(+), found in 36,2% of the analyzed cases, being considered strain more pathogenic. The integrity of cag-PAI was verified in 38,3% of the cases, when considered the three studied markers, however, considering at least one marker of right side (cagA and/or cagE) and the marker of the left side (virB11), the frequency was of 56,4%. The distribution of the genotypes of H. pylori in groups demonstrated that the biggest frequency of strains considered more pathogenic was in tumors of the gastric antrum, did not have predilection of the genotypic variations for none of the histologic types, besides verifying it high frequency of more pathogenic strains in tumor stage II and IV, demonstrating to the participation of H. pylori in gastric carcinogenesis.